(untitled) (Biological Sciences - PJSIR, 2007)
A nti microbi al activity of ethanol, eth y l acetate and hex ane extracts of Nardos/achys jalaman si roots were stu died in vilro again st si x path ogen i c gram pos i tive bacteria ( Slayphylococcu s aureus, Slreplococcus in/ermedius, S faecalis, Ba cillus pumilus , B. cereus, B. sublilus), six gram negative bacteri a ( Escherichia coli, Salmonella typhi, S paralyphi B, Klebsiella pn eumo11iae, Proteus mirabilus, Slzigella jlexneri ) and five fu ngi (Trichophylon rubru111, T schoenleinii, Aspe rgillus 11ige1; Candida albicans, C glabrata ) . Ethanol ic root extract ex hi bited max i mum antimicro bial activ i ty aga i n st al l the tested bacteria and fu ngi , at concentrations of 5, I O and 20 mg/ ml as compared to ethyl acetate an d hexane extract, wh ich d id not show marked activity. A n ti m icrobia l acti vity was com pared wi th the acti vi ties of standard anti bacteria l and an tifu n gal d rugs, name l y Am pic i l l i n and Nystati n , respectivel y. Th e m i n i mu m i n h i bi tory con centrations (MIC) were between 0.5- 1 mg/ ml agai nst a ll the stud ied microor ganisms.